Integrative multi-omics analysis of IFNγ-induced macrophages and atherosclerotic plaques reveals macrophage-dependent STAT1-driven transcription in atherosclerosis - Eskandarian Boroujeni, Mahdi; Lopacinska, Natalia; Antonczyk, Aleksandra; Kluzek, Katarzyna; Wesoly, Joanna; Bluyssen, Hans A. R. (Frontiers in Immunology, 2025)
Atherosclerosis is a chronic inflammatory disease of blood vessels, characterized by atherosclerotic lesions in large- and medium-sized arteries. IFNγ is a crucial mediator of atherosclerosis through activation of signal transducer and activator of transcription (STAT)1. Macrophages (MØ), in different subtypes, play a central role in atherosclerosis, from early foam cell formation to advanced plaque development and potential rupture. Recent evidence in MØ supports a collaborative role of STAT1 with PU.1, in association with histone acetylation and methylation marks, in MØ-specific IFNγ-activated transcriptional responses. This study investigated the role of MØ STAT1-mediated signaling in atherosclerosis progression through multi-omics integration of IFNγ-induced MØ and expression analysis in human and mouse atherosclerotic lesions. First, by integrating ATAC-seq, ChIP-seq, and RNA-seq data from IFNγ-treated and untreated bone marrow-derived MØ, we identified 1139 STAT1-dependent integrative genes. Active transcription of these genes was characterized by prominent promoter STAT1-PU.1 co-binding, increased histone methylation and acetylation and chromatin accessibility. Moreover, KEGG-analysis unraveled a strong connection to lipid metabolism and atherosclerosis-related pathways, whereas STARNET analysis identified high association with LDL cholesterol and diseased vessel traits. Using scRNA-seq data analysis of human carotid and coronary atherosclerotic lesions revealed dynamic changes of STAT1-dependent integrated genes in MØ subtypes, including foamy MØ, monocytes, inflammatory MØ, tissue resident MØ and conventional dendritic cells. Comparative MØ-dependent expression analysis in aortic lesions from LDLr-/- and ApoE-/- high fat diet mouse models substantiated overlap between human and mouse atherosclerosis and identified 24 MØ-specific commonly expressed STAT1-dependent integrated genes. Collectively, we provide detailed insights into MØ-specific IFNγ-activated transcriptional changes, mediated by STAT1-PU.1 co-binding and associated epigenetic changes, and offer the identification of new biomarkers and therapeutic targets in atherosclerosis. Moreover, we present a novel STAT1-dependent gene signature that could potentially serve to monitor MØ-dependent plaque progression during human atherosclerotic disease.